Propelling India from socialist stagnation to global power - Virmani, Arvind, 1949- (New Delhi : Academic Foundation, 2006)
Reviews the economic history of India starting from Independence. This book focusses on policy and institutional reforms to solve identified policy mistakes and problems. It shows that there have been two phases in India's economic history. It shows how India is poised to become a global power.
v. 1. Growth process. -- v. 2. Policy reforms.
Includes bibliographical references and index.
oif 01/09/15
Loan
Keywords: India -- Economic policy -- 1947-; India -- Economic conditions -- 1947-